SesameFG: an integrated database for the functional genomics of sesame - Xin Wei (Nature Portfolio, 2017)
Abstract Sesame (Sesamum indicum L.) has high oil content, a small diploid genome and a short growth period, making it an attractive species for genetic studies on oilseed crops. With the advancement of next-generation sequencing technology, genomics and functional genomics research of sesame has developed quickly in the last few years, and large amounts of data have been generated. However, these results are distributed in many different publications, and there is a lack of integration. To promote functional genomics research of sesame, we collected genetic information combined with comprehensive phenotypic information and integrated them in the web-based database named SesameFG. The current version of SesameFG contains phenotypic information on agronomic traits of 705 sesame accessions, de novo assembled genomes of three sesame varieties, massive numbers of identified SNPs, gene expression profiles of five tissues, gene families, candidate genes for the important agronomic traits and genomic-SSR markers. All phenotypic and genotypic information in SesameFG is available for online queries and can be downloaded freely. SesameFG provides useful search functions and data mining tools, including Genome Browser and local BLAST services. SesameFG is freely accessible at http://ncgr.ac.cn/SesameFG/. SesameFG provides valuable resources and tools for functional genomics research and the molecular breeding of sesame.